Establishing customer knowledge through customer accounting in tourism industry: a study of hotel sector in Malaysia - Majeed Abdulhameed Yasir,; Amizawati Mohd Amir,; Ruhanita Maelah,; Amirul Hafiz Mohd Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The competitive business landscape surrounding the tourism industry inevitably requires significant attention to be placed on maximising the customer base towards establishing a competitive advantage. In this vein, the use of customer accounting has emerged to be a source of crucial information about the customers, which they could assist the management in decision making, managing, and controlling the operation and in turn improve the organisational performance. Considering that, this study aims to articulate and examine the relationships between customer accounting, customer knowledge, and performance. Based on a survey administered to 112 hotel managers, the practice information was collected and analysed using partial least square (PLS). Findings show that among the four dimensions of Customer Accounting, Customer Profitability Analysis, Valuation of Customer as Assets, and Customer Equity Analysis relate significantly to Customer Knowledge, except for the Lifetime Customer Profitability Analysis. Subsequently, only Customer Profitability Analysis and Valuation of Customer as Assets significantly influenced performance. The finding suggests that the adoption of Customer Accounting consisting of combined data about customers may assist the hotels in making decisions to improve their performance. Given that, this study highlighted an accounting technique, that is, Customer Accounting which should be practised by the operators of Malaysian hotels to allow them to manage their customers better, and which is the determinant toward ensuring business success and sustainability.